Analysis of User Satisfaction Level Of E-Pkh Application Using End User Computing Satisfaction (EUCS) Method - anjani, anjani; arin, Pebrinda Andriani; rosa, Rosa Audya; Yogi Kelpin; Kiki Ardila; susanto; bunga intan (ADPEBI, 2022)
Abstract The role of information systems for the government has become an important part, including the Lubuklinggau City Social Service, which has used information technology, one of which is the E-PKH application. So far, the E-PKH application is a digital breakthrough made by the Ministry of Social Affairs based on big data. The E-PKH application is an application that has been issued by the ministry of the republic of Indonesia, this application aims to assist the companion of the family of hope program in updating the data of the beneficiary family (KPM) of the family of hope program. after research, it turns out that the information system on the level of user satisfaction of the E-PKH application at the social service of the city of Lubuklinggau, has not yet attempted an analysis to determine the level of user satisfaction, whether the application is satisfied to be used in operating it. The method and user computing satisfaction (EUCS) is useful in measuring a level of user satisfaction in operating a website or application. The EUCS method can be used to assess and evaluate the use of the website or application based on the experience of the user in operating the website and application. likert. it can be concluded that the results of data processing indicate the level of satisfaction of users of the E-PKH application at the Lubuklinggau City Social Service has reached a valid level. E-PKH application users at the Lubuklinggau City Social Service have an effect on user satisfaction of the E-PKH application, this can be seen in each variable that gets a valid value. Keywords: End User Computing Satisfaction, satisfaction